Involvement of CD8+ T Cells in Multiple Sclerosis - Salou, Marion; Nicol, Bryan; Garcia, Alexandra; Laplaud, David-Axel (Frontiers in Immunology, 2015)
MS (multiple sclerosis) is a chronic autoimmune disease of the central nervous system characterized by focal demyelination patches associated with inflammatory infiltrates containing T lymphocytes. For decades, CD4+ T cells have been recognized as playing a major role in the disease, especially in animal models, which has led to the development of several therapies. However, interest has recently developed in the involvement of CD8+ T cells in MS following the analysis of infiltrating T cells in human brain lesions. A broad range of evidence now suggests that the pathological role of this T cell subset in MS may have been underestimated. In this review, we summarize the literature implicating CD8+ T cells in the pathophysiology of MS. We present data from studies in the fields of genetics, anatomopathology and immunology, mainly in humans but also in animal models of MS. Altogether, this strongly suggests that CD8+ T cells may be major effectors in the disease process, and that the development of treatments specifically targeting this subset would be germane.